1995
DOI: 10.1099/13500872-141-3-645
|View full text |Cite
|
Sign up to set email alerts
|

A putative new peptide synthase operon in Bacillus subtilis: partial characterization

Abstract: A large operon-type structure has been located between the g/tA and citB loci on the Bacillus subtilis chromosome. On the basis of the analysis of the 25 kb sequenced so far, it potentially encodes at least three large proteins which contain structural motifs associated with the subunits of all characterized peptide synthases. The amino acid recognition specificity of this new peptide synthase is discussed in the light of sequence homology with other synthases.Keywords : Bacillus subtilis, peptide synthase ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 3 publications
2
24
0
Order By: Relevance
“…At present, we are able to compare very similar operons, such as surfactin operons of B. subtilis (3) and two lichenysin operons of Bacillus licheniformis (13,45), plipastatin (37,38) and fengycin (16) operons, and iturin A and mycosubtilin (4) operons. These comparisons may provide good techniques for elucidating the boundary of the functional domain that directs engineered peptide synthesis (22,31,33,34).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At present, we are able to compare very similar operons, such as surfactin operons of B. subtilis (3) and two lichenysin operons of Bacillus licheniformis (13,45), plipastatin (37,38) and fengycin (16) operons, and iturin A and mycosubtilin (4) operons. These comparisons may provide good techniques for elucidating the boundary of the functional domain that directs engineered peptide synthesis (22,31,33,34).…”
Section: Discussionmentioning
confidence: 97%
“…The presence of the ␤-amino fatty acid is the most striking characteristic of the iturin A group and distinguishes this group from the other two groups. The operons that encode surfactin (3), plipastatin-fengycin (16,37,38,40), and mycosubtilin (4), which is a member of the iturin A group, have been sequenced and characterized. In particular, a study of the mycosubtilin operon of B. subtilis ATCC 6633 (4) showed that MycA, a novel template enzyme which has functional domain homology to ␤-ketoacyl synthetase and amino transferase and amino adenylation, was present, which implied that MycA is responsible for incorporation of the ␤-amino fatty acid.…”
mentioning
confidence: 99%
“…It may prove to be a useful tool in understanding the primary structures of peptides produced by gene clusters of as-yet-unknown function, such as results from the genome sequencing project of Bacillus subtilis (52). It is also of great interest for crystallographic studies, since such proteins should be as small as possible.…”
Section: Vol 179 1997 Tyrocidine Biosynthesis Operon 6847mentioning
confidence: 99%
“…Z34883 in the EMBL database). Therefore, the amplified fragment contains the sequence encoding the mature PBP4a with an additional N-terminal methionine as well as the endogenous stop codons and putative terminator sequence (25).…”
Section: Resultsmentioning
confidence: 99%
“…Successively referred to as pbp (25) and dacC (19), this gene was overexpressed in Escherichia coli by Pedersen et al (19), who showed that dacC does indeed encode a membrane-bound PBP migrating between PBP4 and PBP5 of B. subtilis on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). This protein is now referred to as PBP4a.…”
mentioning
confidence: 99%